Epidemiology and outcomes of electric burn injury: a study of 768 patients in a high volume tertiary care centre of North India - Srivastava, Sunil; Kumari, Hiranmayi; Singh, Abhimanyu; Rai, Rohit Kumar (International Journal Of Community Medicine And Public Health, 2018)
Background: Electrical burn injuries (EBI) comprise a small proportion of the total burn admissions but they inflict significant morbidity. The objective of this study was to analyse recent epidemiologic data and identify prevention measures. Methods: A retrospective study was conducted by reviewing the medical records of all burn admissions from April 2016 to March 2018 and data was analysed for demographic characteristics and outcomes and patterns of electric burn injury. Results: A total of 3136 admissions were made. Male to female ratio was 1.5:1.0. Rural: urban ratio was 2:1. Mode of injury was accidental (79%), suicidal (12%) and homicidal (9%). Flame burn (64.47%) topped the list of etiologic factors. Electric burn represented 24.49% which was quite significant when compared to other parts of the world. 1042 patients expired (33.22%). Out of the total electric burn admissions, 768 (24.49%) patients were of electric injury. 207 (27.01%) patients sustained low voltage (<1000 kv) injuries while 561 (73.04%) patients had high voltage (>1000 kv) injury. Most of the injuries were work related. There was a rise in serum creatine phosphokinases, myoglobinuria, renal failure, abnormal cardiac events and other concomitant injuries in the high voltage group. Reconstructive surgeries performed in both high and low voltage group was high. A total of 71 (9.24%) fasciotomy and 123 (16.01%) amputations were done. The mortality rate was 10.5%. Conclusions: EBI has a devastating influence on burn survivors. We advocate a low threshold for managing associated injuries, educating safety principles and improving infrastructure by the state to curb this preventable danger.